ICOS ATC N2O Release from Hyltemossa (30.0 m), 2025-05-19–2026-03-31 - Michal Heliasz; Tobias Biermann (Integrated Carbon Observation System, 2026)
Quality-controlled data on molar fraction of atmospheric N2O
Heliasz, M., Biermann, T. (2026). ICOS ATC N2O Release from Hyltemossa (30.0 m), 2025-05-19–2026-03-31, ICOS RI, https://hdl.handle.net/11676/EFb4Ui3DFR7xzHXiNVhkq1Eb
Keywords: Atmosphere Thematic Centre; ICOS; N2O; dry air mole fraction; time instant, UTC; time instant, UTC; quality flag; quality flag; number of points; number of points; standard deviation of gas mole fraction; standard deviation of gas mole fraction; N2O (dry air mole fraction); N2O (dry air mole fraction); Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap